Experimental studies from FT-IR with TG-DTA analysis of ferrites. (2016) - Chitra, S.R.; Sendhilnathan, S.; Gayathri, V.; Sivakumar, M.
Mg0.40 Mn0.60-x Nix Fe2 O4 spinel nanoferrites were obtained by the co-precipitation method. The as-obtained powders were characterised by XRD analysis. All nanoferrite powders obtained from different organic precursors, after synthesising, were pure spinel phase, without secondary phases. TEM and AFM analyses confirmed that the average crystallite size, estimated from Scherrer equation, was the smallest for nanoferrites obtained from a mixture of the compounds and showing their particle size ranging from 20 nm to 50 nm. The prepared nanoferrites were characterised by Fourier transform-infrared spectroscopy (FT-IR), thermogravimetry (TG), differential thermal analysis (DTA) and derivative thermogravity (DTG). The results of these observations are described and discussed.